Enzymatic hydrolysis of plants and algae for extraction of bioactive compounds - Hammed, Ademola Monsur; Jaswir, Irwandi; Amid, Azura; Alam, Md Zahangir; Asiyanbi-H, Tawakalit Tope; Ramli, Nazaruddin (Taylor & Francis, 2013)
Plants and algae contain novel biocompounds with therapeutic potentials. These compounds are either embedded within the cell wall matrix or bonded with polymers at cell cytoplasm, which hinders release of bioactive compounds during extraction. Enzymatic hydrolysis of cell wall and cytoplasm polymers enhances the release of biocompounds while preserving their biological potencies. Previous works have focused more on comparative studies of different enzymes, whereas other process parameters, such as agitation speed, substrate particle sizes, hydrolysis time, degree of hydrolysis, and multistage extraction, have received less attention. This review examines the extent of studies in this area and highlight current research gaps to be explored in future researches.